NuAppFirewall: An Open-Source macOS Application Firewall for Corporate Security - Pachêco, Bianca; Suyungütmüs, Carolina; Truta, José; Delgado, Vinicius; Araújo, Walber; Brunet, João; Domingues Junior, Manoel; Melo, Angela (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2025: Companion Proceedings of the 25th Brazilian Symposium on Cybersecurity, 2025)
Managing network access is essential to ensure the security of both users and corporate ecosystems. On macOS, this control is implemented through Content Filters in firewall applications. However, the state of the practice consists mainly of proprietary consumer tools, while open-source alternatives lack the modularity needed for enterprise adoption. This paper introduces NuAppFirewall, an open-source application firewall developed and deployed in production at Nubank. It includes more than 250,000 automatically generated rules for macOS applications, derived from Nubank’s validated accesses, providing a security foundation that other organizations can leverage for their own implementations.